Embracing change in infrastructure landscapes. (17th February 2023) - Castán Broto, Vanesa; Robin, Enora
Abstract: Infrastructure constitutes a key perspective for the analysis of social change. At the same time, infrastructures exemplify the tension between dynamism and permanence. While they facilitate the constant movement of resource and capital flows, they are also characterised by a visible obduracy that makes them impervious to change. This special issue examines how ideas of change and permanence have been explored in infrastructure studies. It focuses, especially, on the alternatives generated from a landscape perspective. Infrastructure landscape perspectives foreground the complex socio-technical and socio-ecological relations that situate infrastructures in specific conditions and locales. Infrastructure landscape perspectives enable analysis beyond utilitarian perspectives on infrastructure, revealing the range of emotional and cultural attachments that shape them.